Perencanaan Strategis Sistem Informasi Perusahaan - Yayan Cahyan; Muhammad Agreindra Helmiawan; Eggi Julian (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
Company A wishes to develop company information systems and information technology at the management level of each unit because it does not have information systems and technology. Information system strategic planning to support business strategy planning, information system strategy and information technology strategy that is aligned with the needs and demands of the company in achieving its objectives, analysis for the internal and external environment in terms of business and IS / IT by using tools related to Value Chain, SWOT, CSF, BSC, PEST, Five Force and Mc Farlan Strategy Grid and funding sources, the final results include approval of the company's upcoming portfolio application